Religion after Critique: Postcolonial Reflections on the Construction and Effects of Religion - Tayob, Abdulkader 1958- (2024)
In the last few decades, religion and its terms have shown to be implicated in projects of colonial modernity. While this critique of religion is now generally accepted, the term continues to be used in the field with little regard to its history and its colonial construction. This essay aims to bring greater attention to the continuing relevance of religion in contemporary society as articulated in postcolonial scholarship. It proposes closer attention to the critique of religion in the work of David Chidester, Talal Asad and Charles Long. Two distinct dimensions of religion are identified in their work. The first is a construction of religion in colonial modernity, while the second suggests ways of studying religions in light of this construction. I show in this essay that their work points to multiple complementary ways of studying religions in the contemporary. Their work suggests that the field of religious studies cannot ignore its discursive history and construction.
Keywords: Charles Long; David Chidester; Talal Asad; Postcolonialism; critique of religion